The Effect of Hybrid Learning Learning Strategies Applied to the Discovery Learning Model on Student High Order Thinking Skills - Meliana Paryanti; Mufida Nofiana (Universitas Veteran Bangun Nusantara Sukoharjo, 2023)
This study aims to determine the effect of hybrid learning strategies applied to the discovery learning model on students' high order thinking skills. This type of research is quantitative research using quasi-experimental methods. The research design used was post test only control group design. The data collection methods used are tests and documentation. The research instrument used is a test question sheet in the form of multiple-choice questions developed based on the HOTS question grid. There are 2 data analysis techniques used, namely 1) Prasyarta tests include homogeneity tests and normality tests, 2) Hypothesis tests include T-tets tests, F tests, and eta tests. The results showed that from the T-test there was a difference in the average HOTS score of control and experimental class students with sig scores. 0.000, the F test shows that there is an influence with the sig value. 0.000, and the Eta test shows that there is a moderate influence that can be seen from the correlation value of 0.544. It can be concluded from the use of Hybrid learning strategies on students' High Order Thinking Skills shows that there is a moderate influence on increasing student HOTS between control and experimental classes.